2005
DOI: 10.1291/hypres.28.889
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effect of T-Type Calcium Channel Blockers on Endothelial Function in Patients with Essential Hypertension

Abstract: Endothelial function is impaired in essential hypertension. T-type but not L-type voltage-gated Ca

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 30 publications
1
44
0
Order By: Relevance
“…6 However, it is still controversial whether improvement of endothelial function is an effect of the RAS inhibitor class because several investigators were unable to observe such an effect for ARB 7 in spite of beneficial effects seen for other classes of antihypertensives. 8 Basic research has clearly demonstrated that the Ang II-mediated signal transduction pathway induces inflammation and oxidative stress. 9,10 In the clinical setting, ACEI and ARB reportedly improve endothelial function by increasing endothelium-bound (released by heparin injection) extracellular superoxide dismutase (EC-SOD) activity, 6 supporting the above observations.…”
Section: Introductionmentioning
confidence: 99%
“…6 However, it is still controversial whether improvement of endothelial function is an effect of the RAS inhibitor class because several investigators were unable to observe such an effect for ARB 7 in spite of beneficial effects seen for other classes of antihypertensives. 8 Basic research has clearly demonstrated that the Ang II-mediated signal transduction pathway induces inflammation and oxidative stress. 9,10 In the clinical setting, ACEI and ARB reportedly improve endothelial function by increasing endothelium-bound (released by heparin injection) extracellular superoxide dismutase (EC-SOD) activity, 6 supporting the above observations.…”
Section: Introductionmentioning
confidence: 99%
“…Efonidipine improves endothelial function in patients with hypertension when compared with doses of nifedipine that result in comparable decreases in mean blood pressure (9). Therefore, we hypothesized that efonidipine therapy may simultaneously improve endothelial dysfunction, adipocytokine profiles, and other metabolic parameters in nondiabetic patients with hypertension.…”
mentioning
confidence: 99%
“…28,29 In addition, some interventions, including treatment with antihypertensive agents, statins, supplementation therapy, treatment with antioxidants vitamins, and lifestyle modification, have been shown to improve endothelial function and prevent cardiovascular complications. [20][21][22]30,31 Therefore, from a clinical perspective, it is important to estimate the basal condition of endothelial function and of the improvement in endothelial dysfunction.…”
Section: Discussionmentioning
confidence: 99%